2008
DOI: 10.1016/j.neuron.2008.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Antecedents of the Endowment Effect

Abstract: The "endowment effect" refers to the tendency to place greater value on items that one owns-an anomaly that violates the reference-independence assumption of rational choice theories. We investigated neural antecedents of the endowment effect in an event-related functional magnetic resonance imaging (fMRI) study. During scanning, 24 subjects considered six products paired with 18 different prices under buying, choosing, or selling conditions. Subjects showed greater nucleus accumbens (NAcc) activation for pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 43 publications
8
94
0
1
Order By: Relevance
“…While control participants exhibited typical levels of loss aversion, neither of the two amygdaladamaged participants exhibited loss aversion. Also consistent with the notion of self-threat, Knutson et al (2008) found that while participants considered selling, there was a positive correlation between activation in the right insula and estimates of the endowment effect. The insula activation has been observed in participants in other distressing contexts such as unfair ultimatum game offers (Sanfey et al 2003) or social exclusion (Eisenberger, Lieberman, and Williams 2003).…”
Section: Selling As Self-threatsupporting
confidence: 74%
See 1 more Smart Citation
“…While control participants exhibited typical levels of loss aversion, neither of the two amygdaladamaged participants exhibited loss aversion. Also consistent with the notion of self-threat, Knutson et al (2008) found that while participants considered selling, there was a positive correlation between activation in the right insula and estimates of the endowment effect. The insula activation has been observed in participants in other distressing contexts such as unfair ultimatum game offers (Sanfey et al 2003) or social exclusion (Eisenberger, Lieberman, and Williams 2003).…”
Section: Selling As Self-threatsupporting
confidence: 74%
“…As we noted previously, self-reports do not capture loss aversion (Brown 2005), but there is distinct neural activity for loss and gain domains in both risky as well as riskless choice (Knutson et al 2008;Tom et al 2007). Findings from this research, based on the notion of implicit threat and automatic defense response, offer a plausible mechanism for loss aversion: the endowment effect may be a manifestation of self-enhancement due to selfthreat from a forthcoming loss of a self-associated object.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is important insofar as it weighs against a number of potential normative accounts of our data that have been offered to explain related phenomena (33,(54)(55)(56). Rather, to the extent participants were anxious because of a perceived loss, it would be explained only by a reaction to the total loss (i.e., the sum of the unchosen values), a possibility that could plausibly obtain if participants felt "endowed" with the options presented to them on each trial (57,58). Because the predictions of this particular foregone value account are indistinguishable from those of a conflict-based account for any choice between similarly valued items, further experimental data and theoretical models (quantifying the conflict experienced as items vary in overall and relative values) are needed to better adjudicate between these two possibilities.…”
Section: Discussionmentioning
confidence: 83%
“…Toward this goal, as in a previous neuroimaging study (8), we focused on the striatum as our region of interest (ROI). It is well established that the striatum, especially its anterior part (e.g., caudate head and nucleus accumbens), tracks individuals' reported preference for various types of stimuli (8,(11)(12)(13)(14).…”
mentioning
confidence: 99%